2021
DOI: 10.1016/j.ijcha.2021.100809
|View full text |Cite
|
Sign up to set email alerts
|

Predicting survival in patients with acute decompensated heart failure complicated by cardiogenic shock

Abstract: Background Acute decompensated heart failure (ADHF) complicated by cardiogenic shock (CS) has unique pathophysiological background requiring specific patient stratification, management and therapeutic targets. Accordingly, the aim of this study was to derive a simple stratification tool to predict survival in patients with ADHF complicated by CS. Methods and results Using logistic regression, univariable testing was performed to identify the variables potentially associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Reviewing the previous prognostic AHF models, study showed model based on three easy parameters (age, serum creatinine and lactate) was associated with regarding 28-day mortality in the acute decompensated HF complicated by cardiogenic shock. 61 Another study enrolled 1033 AHF patients in emergency setting exhibited elevated troponin and renal function were significant predictors of adverse events. 62 In addition, results via the AHEAD scoring system (A: atrial fibrillation; H: hemoglobin; E: elderly; A: abnormal renal parameters; D: diabetes mellitus) also could be factor in assessing prognosis.…”
mentioning
confidence: 99%
“…Reviewing the previous prognostic AHF models, study showed model based on three easy parameters (age, serum creatinine and lactate) was associated with regarding 28-day mortality in the acute decompensated HF complicated by cardiogenic shock. 61 Another study enrolled 1033 AHF patients in emergency setting exhibited elevated troponin and renal function were significant predictors of adverse events. 62 In addition, results via the AHEAD scoring system (A: atrial fibrillation; H: hemoglobin; E: elderly; A: abnormal renal parameters; D: diabetes mellitus) also could be factor in assessing prognosis.…”
mentioning
confidence: 99%
“…To date, there is a relative lack of consensus on which factors are key for the determination of patients with AHF. Some studies reported that demographic information (age), clinical manifestations (NYHA functional class, SBP, DBP, and MAP), pre‐existing conditions (diabetes mellitus and AF), medications (vasopressors), laboratory tests (NT‐proBNP, haemoglobin, sodium, albumin, creatinine, blood urea nitrogen, and eGFR), and 12‐lead resting ECG (RBBB) were significantly associated with OS 8,9,37–40 . However, in the other studies, there was no apparent association of demographic information (age), clinical manifestations (SBP and DBP), pre‐existing conditions (AF), medications, and laboratory tests (NT‐proBNP, haemoglobin, sodium, and creatinine) with long‐term survival 41–43 .…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it is worth noting that the current body of evidence concerning the impact of CS teams on outcomes specifically related to Acute Decompensated Heart Failure with Cardiogenic Shock (ADHF-CS) patients is notably limited. Recent research has highlighted a rising prevalence of ADHF-CS when compared to cases of AMI-CS 46 . Consequently, further research in this realm is imperative to enhance our understanding of the distinct implications and benefits of CS teams for ADHF-CS patients.…”
Section: Discussionmentioning
confidence: 99%